EFFECT OF ARBUSCULAR MYCORRHIZAL FUNGI AND FERTILIZATION ON GROWTH OF SEEDLINGS OF Eugenia uniflora L., PRODUCED IN DIFFERENT SUBSTRATES - Dalanhol, Samanta Jaqueline [UNESP]; Nogueira, Antonio Carlos; Gaiad, Sergio; Kratz, Dagma (Soc Brasileira Fruticultura, 2016)
The aim of this study was to evaluate the effect of mycorrhizal fungi (AMF), the fertilization and substrate composition on growth of seedlings of Eugenia uniflora. The seeds were germinated in vermiculite and transplanted to plastic tubes (100 cm(3)) containing substrates with vermicompost and carbonized rice hull, and as a control, we used the commercial substrate prepared with pine bark. These substrates were tested with and without mycorrhizal inoculation, added to the substrate, but also tested the presence and absence of fertilization. The physicochemical properties of formulated substrates were analyzed. Were evaluated height, stem diameter, aggregation of roots to the substrate, air dry biomass, radicial dry biomass and were determined the relationship between height and stem diameter and Dickson quality index. Inoculation with AMF did not influence the growth of seedlings, whereas the interaction between substrates and fertilization was significant for most variables. The lack of response to AMF was probably due to high concentrations of phosphorus in these substrates. It was concluded that the substrate with vermicompost and carbonized rice hulls in the ratio of 20/80 can be used in the production of seedlings of this species.
Keywords: pitanga; mycorrhiza; vermicompost; carbonized rice hulls